Back to the Unchanging Past. (6th November 2015) - Baron, Sam
Abstract: The standard philosophical view of time travel has it that time travelers cannot change the past. It has been argued by some that the standard view is false, and that this can be shown using a two‐dimensional model of time. I defend the standard view against this attack. I show, first, that the addition of a second temporal dimension does not provide a model of changing the past and, second, that neither does the addition of n temporal dimensions for any n > 1.